The Influence of Online Training and Compensation on Employee Performance(A Study on Employee of eFishery Start-up) - Lestary, Fungky; Dyahrini, Wien (IJSM, 2025)
This study aims to evaluate the impact of online-based training and compensation on employee performance within the operational division of eFishery, a technology-driven agritech startup in Indonesia. The primary motivation for this research stems from operational performance issues related to the effectiveness of training programs and compensation structures. The study focuses on identifying the direct relationship between online training and forms of compensation on the quality of employee performance, emphasizing the importance of competence enhancement as a strategic effort to boost productivity in a digital environment. A quantitative approach was employed, with data collected through a survey method targeting all employees in the operational division. Multiple linear regression analysis was utilized to test the influence of independent variables on the dependent variable. The findings indicate that online training and compensation significantly and positively contribute to improved employee performance. This study enriches human resource management literature, particularly in the context of employee development within the startup industry, and provides practical implications for organizations in formulating effective training strategies and compensation systems.